ANALISIS SEGMENTASI DEMOGRAFIS DAN PERILAKU PADA BISNIS PARIWISATA - Aldi Adianta; Suprihatin Ali; Prasetya Nugraha (Jurusan Administrasi Bisnis, FISIP, Universitas Lampung, 2019)
Analyzing business segmentation of Taman Wisata Bukit Mas Cottage & Resto in Bandar Lampung was the purpose for this research. Descriptive research using clustering technic analysis. Visitors divided into three cluster based on demography and behavior. The results showed average visitors in middle class to down, which came for refreshing or holiday, either gathering with friends or family, or even for enjoying the scenery. It stressed on how important for the company to understand the consumer’s profile that can help identify its market segmentation, and design appropriate programs for expected target segmentation.